Copper‐Catalyzed C‐4 Carboxylation of 1‐Naphthylamide Derivatives with CBr4/MeOH. Issue 17 (12th July 2019) - Sahoo, Tapan; Sen, Chiranjit; Singh, Harshvardhan; Suresh, E.; Ghosh, Subhash Chandra
Abstract: A simple and practical copper catalyzed C‐4 carboxylation reaction of 1‐naphthylamide derivatives using carbon tetra bromide and methanol is reported here. Picolinamide and its derivatives are used as a bidentate directing group for the distal C4‐H functionalization. Various substituted naphthylamide derivatives, and anilides are employed for the carboxylation and proceeds in good yields under mild condition. From the outcome of experimental results, it is proposed that C4‐H carboxylation reaction of 1‐naphthylamides might proceed through a single electron transfer (SET) pathway. Abstract :